The Role of Pituitary Adenylate Cyclase-Activating Polypeptide (PACAP) Signaling in the Hippocampal Dentate Gyrus - Johnson, Gregory C.; Parsons, Rodney; May, Victor; Hammack, Sayamwong E. (Frontiers in Cellular Neuroscience, 2020)
Pituitary adenylate cyclase activating polypeptide (PACAP, ADCYAP1) dysregulation has been associated with multiple stress-related psychopathologies that may be associated with altered hippocampal function. In coherence, PACAP- and PAC1 receptor (ADCYAP1R1)-null mice demonstrate changes in hippocampal-dependent behavioral responses, implicating PACAPergic system function in this structure. Within the hippocampus, the dentate gyrus (DG) may play an important role in discerning the differences between similar contexts, and DG granule cells appear to both receive input from PACAP-expressing terminals and highly express PAC1 receptors. Here we review the evidence from our own laboratories and others that PACAP is an important regulator of activity within hippocampal circuits, particularly within the DG. These data are consistent with an increasing literature implicating PACAP circuits in stress-related pathologies such as post-traumatic stress disorder (PTSD), and implicate the hippocampus, and in particular the DG, as a critical site in which PACAP dysregulation can alter stress-related behaviors.